Lower Urinary Tract Symptoms are Associated with Erectile Function and Psychological Symptoms in Men with Late‐Onset Hypogonadism Syndrome. Issue 3 (16th September 2013) - SHIGEHARA, Kazuyoshi; SUGIMOTO, Kazuhiro; KONAKA, Hiroyuki; MAEDA, Yuji; KITAGAWA, Yasuhide; MIZOKAMI, Atsushi; KOH, Eitetsu; NAMIKI, Mikio
<x xml:space="preserve">Abstract</x> Objective We assessed the factors significantly associated with lower urinary tract symptoms (LUTS) in men with late‐onset hypogonadism (LOH) syndrome. Methods The study population consisted of 258 patients aged 40 years or older diagnosed with LOH syndrome. Each patient completed a questionnaire study, such as the International Index of Erectile Function (IIEF) 5, Aging Male Score (AMS), and International Prostate Symptom Score (IPSS). Body mass index (BMI), waist size, and muscle volume were measured in all patients, and blood biochemical data, including total cholesterol, triglyceride, hemoglobin A1c, and free testosterone (free T), were also collected. We analyzed the factors that have effect on IPSS. Results The mean age of the patients was 64.9 ± 8.7 years, and the mean free T value was 7.3 ± 2.2 pg/mL. The critical factors affecting IPSS were IIEF5 score, BMI, muscle volume, age, AMS, and free T‐value (P < 0.05). Age showed the strongest significant positive correlation with IPSS (r = 0.321, P < 0.001). Each factor was controlled for age. IIEF5 score and AMS were independent factors affecting IPSS (r = −0.221 and 0.195, respectively, P < 0.05). IPSS showed an inverse correlation with IIEF5, and a positive correlation with AMS. LUTS also had a weak negative correlation with Free T‐value but this was not significant (r = −0.121, P = 0.061). Conclusion Lower urinary tract symptoms were significantly correlated with erectile function and psychological symptoms in men with LOH syndrome.